Helical tomotherapy for post-mastectomy radiation therapy with or without breast implant: a single institution experience. (July 2022) - Dejean, Romain; Chaltiel, Leonor; Izar, Françoise; Chira, Ciprian; Leray, Helene; Jouve, Eva; Simon, Luc; Massabeau, Carole
Highlights: We report very low doses to the heart and lung for PMRT with Helical Tomotherapy. Breast implant improves dosimetric results with reduced heart and lung doses. No local recurrence was seen in the posterior part of implants. Abstract: Introduction: We report on our experience of using Helical Tomotherapy (HT) in the context of post-mastectomy radiation therapy (PMRT) with or without immediate implant-based breast Reconstruction (IBR). Material and methods: The study included a total of 173 patients who underwent PMRT with HT between 2013 and 2015 in our institution (87 immediate breast reconstructions with retropectoral implants (IBR + ), 86 without reconstructions (IBR-)). The chest wall target volume included subcutaneous tissue and pectoralis muscle and excluded the posterior region of the implant as well as the ribs. Results: Median time to initiation of the first adjuvant treatment from mastectomy was similar between the two groups (p = 0.134). Dose coverage to the chest wall was significantly improved for the IBR + group (V95% = 95.1 % versus 92.0 %; p < 0.0001). The irradiated volume of the ipsilateral lung was significantly decreased in the IBR + group with a median V20Gy of 11.6 %, compared to 15.2 % for the control group (p < 0.0001). The median heart V15Gy was also significantly lower in the IBR + group than in the control group (1.7 vs 2.5 %; p = 0.0280). The reconstruction failure rate was 14.9% (n = 13). After a median follow-up of 65 months, loco regional recurrence rate was low in both groups: 3 patients (3.4%) in the IBR + group and 5 patients (5.8%) in the control group, without any local recurrence in the posterior part of the implant. Conclusions: The presence of a breast implant reduces cardiac and pulmonary doses during Tomotherapy irradiation, without compromising oncological outcomes.